Increased Population Risk of AIP‐Related Acromegaly and Gigantism in Ireland. Issue 1 (4th October 2016) - Radian, Serban; Diekmann, Yoan; Gabrovska, Plamena; Holland, Brendan; Bradley, Lisa; Wallace, Helen; Stals, Karen; Bussell, Anna‐Marie; McGurren, Karen; Cuesta, Martin; Ryan, Anthony W.; Herincs, Maria; et al.
Abstract : Combining patient and general population screening in Ireland with a novel coalescent‐based population genetics approach, we revealed that AIP ‐related pituitary adenomas are frequent in Mid Ulster region of Northern Ireland and almost exclusively due to a founder AIP mutation, R304 * . Forward simulation predicted many undiagnosed carriers. We demonstrated that geographically‐targeted population screening complements clinical testing for carrier identification. Benefitting from patient and general public involvement, our study contributed to disease awareness locally, necessary for early diagnosis and improved patient outcomes. ABSTRACT: The aryl hydrocarbon receptor interacting protein ( AIP ) founder mutation R304 * (or p.R304 * ; NM_003977.3:c.910C>T, p.Arg304Ter) identified in Northern Ireland (NI) predisposes to acromegaly/gigantism; its population health impact remains unexplored. We measured R304 * carrier frequency in 936 Mid Ulster, 1, 000 Greater Belfast (both in NI) and 2, 094 Republic of Ireland (ROI) volunteers and in 116 NI or ROI acromegaly/gigantism patients. Carrier frequencies were 0.0064 in Mid Ulster (95%CI = 0.0027–0.013; P = 0.0005 vs. ROI), 0.001 in Greater Belfast (0.00011–0.0047) and zero in ROI (0–0.0014). R304 * prevalence was elevated in acromegaly/gigantism patients in NI (11/87, 12.6%, P < 0.05), but not in ROI (2/29, 6.8%) versus non‐Irish patients (0–2.41%). Haploblock conservation supported a common ancestor for all the 18 identified Irish pedigrees (81 carriers, 30 affected). Time to most recent common ancestor (tMRCA) was 2550 (1, 275–5, 000) years. tMRCA‐based simulations predicted 432 (90–5, 175) current carriers, including 86 affected (18–1, 035) for 20% penetrance. In conclusion, R304 * is frequent in Mid Ulster, resulting in numerous acromegaly/gigantism cases. tMRCA is consistent with historical/folklore accounts of Irish giants. Forward simulations predict many undetected carriers; geographically targeted population screening improves asymptomatic carrier identification, complementing clinical testing of patients/relatives. We generated disease awareness locally, necessary for early diagnosis and improved outcomes of AIP ‐related disease.